2020
DOI: 10.22454/fammed.2020.470334
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Medical School Admissions: A Strategic Process for Meeting Our Social Mission

Abstract: Background and Objectives: Increased medical school class sizes and new medical schools have not addressed the workforce inadequacies in primary care or underserved settings. While there is substantial evidence that student attributes predict practice specialty and location, little is known about how schools use these factors in admissions processes. We sought to describe admissions strategies to recruit students likely to practice in primary care or underserved settings. Methods: We surveyed admissions person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Unfortunately, the significant decline in medical school enrollment of rural students (Jaret, 2020; Shipman et al, 2019) indicates a critical need to build, strengthen, and support the rural pipeline. To address this, many medical schools in the United States have implemented targeted recruitment and mission-based admissions to attract students from rural backgrounds (Evans et al, 2020; Schmitz et al, 2020). Longenecker et al (2020) found that although fewer than 10% of medical schools explicitly commit to producing rural physicians, nearly 65% provide some rural clinical experiences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Unfortunately, the significant decline in medical school enrollment of rural students (Jaret, 2020; Shipman et al, 2019) indicates a critical need to build, strengthen, and support the rural pipeline. To address this, many medical schools in the United States have implemented targeted recruitment and mission-based admissions to attract students from rural backgrounds (Evans et al, 2020; Schmitz et al, 2020). Longenecker et al (2020) found that although fewer than 10% of medical schools explicitly commit to producing rural physicians, nearly 65% provide some rural clinical experiences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The former President of South Africa, Nelson Rolihlahla Mandela, once said “Education is the most powerful weapon which you can use to change the world.” [ 34 ]. Neither the United States [ 35 ] nor Ireland [ 36 ] solved its problem of retaining its medical workforce for underserved areas by increasing the numbers of medical students. The qualities of doctors proved to be more important.…”
Section: The Root Stem Model Of Health Worker’s Retentionmentioning
confidence: 99%
“…Worldwide most medical schools remain in urban areas [ 35 , 39 ] and adapt medical students to urban environments. Medical schools could establish satellite rural campuses for at least some courses.…”
Section: The Root Stem Model Of Health Worker’s Retentionmentioning
confidence: 99%
“…Correcting the existing workforce shortages in rural America with intentional family medicine GME will save lives while contributing to the economic basis of local health care, keeping both patients and health care economic investment close to home. Literature exists addressing the rural placement rates as related to admission of students, 4 undergraduate medical education, 5 recruitment, and retention strategies employed. 6 As we take up our role in GME for rural practice, 7 the core concept of situational adaptation applies.…”
Section: Commentarymentioning
confidence: 99%